Effects of shoeing on forelimb swing phase kinetics of trotting horses - Singleton, W. H.; Clayton, H. M.; Lanovaz, J. L.; Prades, M. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
The objective of this study was to compare swing phase phase kinetics in the equine forelimb under three shoeing conditions: unshod, flat shoes, eggbar shoes. Flat shoes and eggbar shoes were matched for weight. A 60 Hz video camera recorded a full trotting stride in the sagittal plane during three passes per horse for each shoeing condition. A general linear model ANOVA, treating the horse as a random variable was used to detect differences (p <0.05) between shoeing conditions. All of the joints showed significant differences in net joint moments and energy bursts, between the two shod conditions versus unshod, but differences were not evident between flat shoes and eggbar shoes. When the horses were shod the elbow flexors generated more energy in the early swing phase in order to overcome the increased inertia associated with the weight of the shoes; and the elbow extensors generated more energy in late swing phase to overcome the increased momentum of the shod hoof as it was swung forward. In the distal limb in the early swing phase, energy absorption increased on the extensor (dorsal) aspect, to control joint flexion, and in the late swing phase on the flexor (palmar) aspect to control forward motion and extension. It is concluded as a consequence of changing the inertial parameters of the hoof that the weight of the shoes altered the limb kinetics of trotting horses.
Keywords: Animation; moments; powers; energies; inertial parameters